Experimental investigation on the damage mechanical proper-ties of red sandstone under freeze-thaw cycles - Zeng, Peng; Ren, Yonglin; Zhao, Kui; Yang, Xianda; Huang, Zhen; Li, Yanda; Xiong, Liangfeng; Gong, Cong (Frontiers in Materials, 2025)
In rock engineering problems, varying durations of freeze-thaw cycles (FTC) can influence the physical and mechanical properties of rocks, potentially inducing engineering hazards. This study investigated these effects through FTC tests and uniaxial compression acoustic emission (AE) tests on red sandstone by analyzing the impacts of freeze–thaw duration and cycle count on the physical and mechanical properties and AE characteristics of the sandstone. Additionally, damage evolution was quantitatively analyzed using AE cumulative counts. The results show that peak stress, elastic modulus, and longitudinal wave velocity reduction rate positively correlate with freeze–thaw duration and cycle count. However, a negative correlation is observed with porosity. The ib value obtained by AE generally shows the change rule of “progressive increase–gradual decline–subsequent resurgence–sharp plummet.” The maximum value of the rising stage (ib1), the minimum value of the falling stage (ib2), and the maximum value of the rising stage (ib3) are positively correlated with the FTC time but negatively correlated with cycle count. Furthermore, the proportion of AE cumulative counts rate in the growth stage of rock failure increases exponentially with the duration and number of FTCs. As FTCs progress, the micro–cracks inside the rock gradually shift from tensile cracks to shear cracks, with a faster transition observed under longer freeze–thaw durations. The damage variable exhibits mutation or gradual mutation, increasing progressively with freeze–thaw duration and cycle count. This study elucidates the damage mechanisms of red sandstone induced by FTC duration, revealing the crack mode transition and associated AE characteristics. These results provide valuable insights for stability analysis, control, and design considerations in rock engineering projects within freeze–thaw environments.